(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The purpose of this article is to identify and describe the elements, principles of teaching an innovative cluster approach that contribute to the development of S-competence (i.e. the necessary knowledge, skills, attitudes and values) related to the core subjects of STEAM, and potential approaches to STEAM teaching that need to be taken into account for the effective implementation of STEAM in the curriculum. The article extensively covers the implementation of the Steam methodology based on the cluster approach.